Thermal Insulation Properties of Microfibrillated Cellulose Aerogel - YANG Simin; LUO Xinrong; AN Yuying; TU Lexi; SHEN Hua (东华大学学报（英文版）, 2021)
TS102.1; Microfibrillated cellulose ( MFC ) aerogels are bio-based materials with high thermal resistance. In this study, MFC aerogels and MFC-kapok composite aerogels were prepared. A series of experiments were carried out in a climate chamber to study the influence of MFC concentration, the temperature gradient, testing methods and introduction of kapok fibers on the thermal insulation properties of aerogels. The results suggested that the density of MFC aerogels was less than 10 mg/cm3 and the porosity was higher than 99％. Besides, the minimum thermal conductivity of MFC aerogels was 0.0357 W·m-1·K-1 observed at 0.8％MFC aerogels. The minimum thermal conductivity of MFC-kapok composite aerogels was 0.0382 W·m-1 · K-1 when the ratio of MFC to kapok was 2 :6.